The Role of Women in Supporting the Economy through Woven Bamboo - Benedhikta Kikky Vuspitasari; Veneranda Rini Hapsari; Shanti Veronica Br Siahaan (Business Finence Analyst Co.,, 2023)
The purpose of this study is to describe the role of women in supporting the economy through woven bamboo, this type of research is descriptive qualitative, the results of the study illustrate that women who are involved in woven bamboo are able to create job and income opportunities for themselves and their families. able to manage a business so as to form an entrepreneurial spirit. Through woven bamboo, women can experience economic empowerment which includes financial autonomy, increased social status, and influence in decision making. Women who have access to bamboo weaving skills can increase their independence in managing personal and family finances. Woven bamboo is an integral part of the cultural heritage of a society. Women involved in woven bamboo play an important role in the preservation of this tradition. They maintain the woven techniques that have been passed down from generation to generation, and preserve the designs, motifs and stories associated with woven bamboo. In this case, they maintain their local cultural identity and respect their ancestral heritage. Woven bamboo also has a positive impact on the environment. Bamboo is an environmentally friendly material because it is a fast growing plant and can be renewed easily. By using bamboo as the main material for woven bamboo craftswomen help reduce the use of synthetic materials that have a negative impact on the environment. It also contributes to the promotion of a sustainable and environmentally friendly lifestyle. Through their role in woven bamboo, women make a real contribution to the local economy, safeguard cultural heritage and promote a sustainable environment.